2020
DOI: 10.1136/bmjopen-2019-036094
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for peer first response to mining emergencies resulting in injuries: a cross-sectional study

Abstract: ObjectiveIdentify factors of preparedness for peer first response to underground mining emergencies with injured victims.DesignCross-sectional questionnaire study of Swedish underground mineworkers.SettingSeven out of nine Swedish underground mines.ParticipantsA total of 741 mineworkers out of 1022 (73%) participated in this study.InterventionsNone.Outcome measuresLevel of preparedness for emergencies with injuries in underground mines.ResultsThree factors influenced the preparedness of mineworkers for a peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Teir training consisted of in-person instruction following the Peyton 4-stage model and simulation-based mastery learning with deliberate practice on certifed simulators of amputated limbs [42]. While earlier research has noted the importance of educational interventions in the domain of self-efcacy in bleeding control training [43,44], our fndings have important implications for developing similar results in self-confdence and self-efcacy among nursing students utilising a low-cost simulator. In this vein and as mentioned in the literature, participants are able to attain nearly fawless competency scores and appropriately assist a bleeding victim by applying direct pressure [45], particularly when HFS or more realistic models are being used, with no major fnancial expenditure [46].…”
Section: Discussionmentioning
confidence: 76%
“…Teir training consisted of in-person instruction following the Peyton 4-stage model and simulation-based mastery learning with deliberate practice on certifed simulators of amputated limbs [42]. While earlier research has noted the importance of educational interventions in the domain of self-efcacy in bleeding control training [43,44], our fndings have important implications for developing similar results in self-confdence and self-efcacy among nursing students utilising a low-cost simulator. In this vein and as mentioned in the literature, participants are able to attain nearly fawless competency scores and appropriately assist a bleeding victim by applying direct pressure [45], particularly when HFS or more realistic models are being used, with no major fnancial expenditure [46].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, there are differences in cognition among workers of different working ages and positions [ 17 ]. An interesting cross-sectional questionnaire study of Swedish underground mineworkers showed that familiarity with rescue procedures, cognition of emergencies with injuries, and experience with using equipment influence the preparedness of mineworkers for a peer first response [ 18 ]. There are obvious cognitive barriers to using new safety and health technologies between workers and managers, and the differences are revealed in terms of readiness, cognition, and initial trust with respect to using various technologies [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%